Numerical analysis of a reactivity controlled compression ignition engine - Görmez, Gonca; Ceper, Bilge Albayrak (Elsevier Ltd, 2021)
Nowadays, internal combustion engines have great importance due to the increasing need for vehicles. Since the engines in the vehicles cause air pollution, different combustion strategies are being tried more and more every day. Emissions are aimed to be reduced thanks to the reactivity controlled "compression ignition (RCCI) engine", which is one of the low temperature combustion strategies. In this study, Continental AVDS 1790-2A tank engine was numerically investigated for gasoline/diesel fuels at RCCI combustion mode. Ansys-Fluent and GT-Power programs were used for numerical analysis. Different lambda values (2.0, 2.5 and 3.0), different exhaust gas recirculation (EGR) values 0%, 30%, and 50% and different start of injection (SOI) timing (340 degrees, 345 degrees and 347 degrees CA) parameters were evaluated. In RCCI combustion mode values were obtained closest to the conventional diesel combustion pressure value at lambda = 2.5, EGR = 30% and SOI = 340 degrees CA.
Keywords: RCCI; Computational fluid dynamics; EGR; Injection timing